2022
DOI: 10.3389/fpsyg.2022.854909
|View full text |Cite
|
Sign up to set email alerts
|

How Ice Rink Locations Affect Performance Time in Short-Track Speed Skating

Abstract: PurposeTo accurately provide evaluations on how match performance for elite skaters in short track speed skating developed, and whether geographical factors of ice rink locations should be considered apart from technical abilities. We created a dataset containing competition records from the 2013–14 to 2020–21 seasons (500 m event) on the official website.MethodsOne-way ANOVA was applied to statistically analyze whether the best performance times exhibited significant differences in varied hosting cities. Perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Figure 7 illustrates that higher rink altitudes correspond to an enhancement in race performance. This observation aligns with previous studies (2,3,4). For instance, Muehlbauer et al (5) demonstrated that at high altitudes, skaters exhibit shorter time per split lap (p < 0.001), resulting in a shorter total time.…”
Section: Ice Rink Altitudesupporting
confidence: 94%
See 2 more Smart Citations
“…Figure 7 illustrates that higher rink altitudes correspond to an enhancement in race performance. This observation aligns with previous studies (2,3,4). For instance, Muehlbauer et al (5) demonstrated that at high altitudes, skaters exhibit shorter time per split lap (p < 0.001), resulting in a shorter total time.…”
Section: Ice Rink Altitudesupporting
confidence: 94%
“…latitude, and oxygen concentration (1)(2)(3)(4). Additionally, subjective factors, like athletes' technical abilities involving strength, mass, and motor behavior (6,7), along with game strategy (8), have demonstrated a notable impact on game performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation